Re-visiting Orientalism: on the problem of speaking for the Orient - Baradan, Saad Nawras, author; Kneller, Jane, advisor; Didier, John, committee member; MacDonald, Bradley, committee member (Colorado State University. Libraries, 2015)
It was the advice of one of my professors that when I found a thesis topic that would sustain my interest that I be able to summarize it in one sentence. Here it is: Orientalism involves instances of speaking for others, and, therefore, Orientalism is primarily a problem of ethics. Or, in another formulation: Orientalism, not as the problem of representing the Orient, but as the problem of speaking for the Orient. In the pages that follow, I will offer a re-reading of Orientalism, one that is aimed at both a positive exegesis of Edward Said’s Orientalism and a critical engagement with the text. In the first chapter, I distill Orientalism and some of the common criticisms leveled against the book. This requires delving into Michel Foucault and specifically examining how Said appropriates Foucault’s discourse theory. My main argument here will be that discourse theory is by its nature perspectival, and, thus, Said does not fail to correctly appropriate Foucault. Given the perspectival nature of discourse theory there are numerous perspectives from which to analyze the discourse of Orientalism. Thus, my suggestion by the end of this chapter is to make the turn away from a representational reading of Orientalism towards an ethical reading. In Chapter Two, I chart out this ethical reading by highlighting the problem of Orientalism as one of speaking for the Orient rather than representing the Orient. Using Linda Martin Alcoff’s essay, The Problem of Speaking for Others, I highlight how discourse theory in general and Orientalism in particular involve instances of speaking for others. In Chapter Three, then, I offer solutions to the vexed problem of speaking for others.